Teaching social technologies literacy for empowerment and everyday life - Saorín, Tomás; Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2014)
Numerous social-oriented collaborative technologies, called social technologies, are presented within the framework of digital literacy. They have an impact in the empowerment and self-organization of individuals and groups as they set their own goals and increase their influence in public opinion. These digital platforms also help to obtain practical outcomes by new forms of interchange